Imunodetekce v laterálním toku na membráně - Göselová, Sandra; Krausová, Martina; Holubová, Barbora; Karamonová, Ludmila; Rauch, Pavel (Chemické listy, 2014)
The review focuses on the latest development of the title method. Compared with conventional instrumental techniques the method is simple and fast. It can be used for qualitative and/or semiquatitative detection and should be applied in non-laboratory environment. The principles of current formats, different markers, such as gold, carbon, and latex nanoparticles as well as possible quantitative monitoring are described. The applications generally include tests for low- or high-molecular-weight compounds, such as pesticides, drugs, mycotoxins, hormones, allergens, pathogens and metabolites in food or feed, as well as veterinary, biomedical and environmental purposes.
Keywords: Gold; Chemistry Techniques, Analytical; Electronic Data Processing; imunoanalýza; nanočástice; pesticidy; Immunoassay; metody pro přípravu analytických vzorků; Analytic Sample Preparation Methods; imunoenzymatické techniky; uhlík; Nanoparticles; Pesticides; Allergens; Bacterial Toxins; alergeny; automatizované zpracování dat; Radioimmunoprecipitation Assay; soudní toxikologie; Carbon; bakteriální toxiny; chemické techniky analytické; Forensic Toxicology; Immunoenzyme Techniques; Immunochemistry; zlato; radioimunoprecipitační analýza; imunochemie